2017
DOI: 10.1016/j.jsha.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Ramadan fasting on patients with prosthetic heart valve taking warfarin for anticoagulation

Abstract: No significant difference in mean INR or warfarin dose was found and a better quality of anticoagulation was achieved during Ramadan. A tendency toward supra-therapeutic anticoagulation occurred after Ramadan, thus a closer follow up during this period may be reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
3
6
1
Order By: Relevance
“…This finding is consistent with the result of a prior study on 70 patients with mechanical prosthetic heart valves, conducted in Egypt and showed no significant difference in the mean INR levels during and after Ramadan (8). A similar result was also concluded from a recently conducted prospective study from Turkey, where INR level was checked on a weekly basis for 3 months including Ramadan (7). In contrary to our findings, there are two other studies which have reported a significant increase in the mean INR during Ramadan (5,7).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is consistent with the result of a prior study on 70 patients with mechanical prosthetic heart valves, conducted in Egypt and showed no significant difference in the mean INR levels during and after Ramadan (8). A similar result was also concluded from a recently conducted prospective study from Turkey, where INR level was checked on a weekly basis for 3 months including Ramadan (7). In contrary to our findings, there are two other studies which have reported a significant increase in the mean INR during Ramadan (5,7).…”
Section: Discussionsupporting
confidence: 86%
“…Available studies on the effect of Fasting on the International Normalized Ratio (INR) were conducted in different geographic areas of the world, not including Saudi Arabia. These studies included diverse patient populations with widely variable cultural and social backgrounds and ended up by inconsistent results (5)(6)(7)(8). Our study came to evaluate this unresolved issue in the Saudi community, using a larger sample size of a more homogeneous population.…”
mentioning
confidence: 99%
“…Studies assessing the effect of Ramadan fasting on warfarin are limited. A recent study from Turkey in just 18 patients observed no significant change either in the warfarin doses or in the PT‐INR during Ramadan period and increased tendency to achieve supratherapeutic range subsequently 5 . Additionally, the authors have also observed greater proportion of patients in the therapeutic range during Ramadan.…”
Section: Discussionmentioning
confidence: 89%
“…On the contrary, another report on patients with prosthetic valve replacements on warfarin reported no significant changes in the PT‐INR during Ramadan 4 . Similarly, another study on 18 patients reported a similar PT‐INR range during Ramadan, but a greater risk of supratherapeutic anticoagulation was observed in the month following Ramadan 5 . No significant differences were observed in a 5‐year prospective study on 289 patients receiving warfarin 6 .…”
Section: What Is Known and Objectivementioning
confidence: 88%
“…Moreover, closer monitoring or a dosage adjustment may be necessary during fasting in patients with higher end of INR target ranges or at increased risk of bleeding [148]. Similarly, a recent prospective study also suggested for closer follow-up of fasting patients who are on warfarin therapy [149]. Moreover, a pilot study also demonstrated that fasting deeply affects the stability of INR and increases the risk of bleeding in patients treated long-term with acenocoumarol [150].…”
Section: Indian Recommendationmentioning
confidence: 99%